A Simulation Model for Applying Audit-Sampling Techniques. - Walgenbach, Paul H.; Frank, Werner G. (The Accounting Review, 1971)
Problem recognition and formulation are usually more difficult than problem solution. However, problem recognition situations are difficult to devise, and educators in most cases seem to rely on structured problems or other prescription approaches. During the past two years a computer-simulation project has been used in auditing classes at the University of Wisconsin, principally to provide an unstructured approach to the study of sampling and confirmation techniques. This paper provides a description of such a simulation.